1979
DOI: 10.3382/ps.0580372
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Binding Protein in the Intestine of the Chicken

Abstract: The mucosa of the mesenteric intestine of the chicken has been found to contain a fatty acid binding protein (FABP) with a molecular weight of less than 12,400. The protein is present in the newly hatched chick before ingestion of feed and in the adult bird. When a low-fat diet is fed, the concentration of the FABP is highest in the proximal portion of the intestine and decreases posteriorly. When a high-fat diet is fed, an increase occurs in the amount of FABP in the lower section of the intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Thus, there may be two mechanisms involved: 1) a slower ROP and 2) a further development of absorptive mechanisms. Additional evidence for the latter to be a determining factor is existence of a fatty acid binding protein in the intestine of chickens (Katongole and March, 1979) whose activity increases with age in young chicks (Katongole and March, 1980). Also, Katongole and March (1980) found that NaT increased the activity of fatty acid binding protein, an additional factor to add support to the favorable influence of bile acids on absorption of lipid.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, there may be two mechanisms involved: 1) a slower ROP and 2) a further development of absorptive mechanisms. Additional evidence for the latter to be a determining factor is existence of a fatty acid binding protein in the intestine of chickens (Katongole and March, 1979) whose activity increases with age in young chicks (Katongole and March, 1980). Also, Katongole and March (1980) found that NaT increased the activity of fatty acid binding protein, an additional factor to add support to the favorable influence of bile acids on absorption of lipid.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, there has to be something in bile that enables fatty acids from corn to be better utilized than those from tallow. Katongle and March (1979) demonstrated the existence of a fatty acid binding protein (FABP) in chickens. They also noted that bile acids stimulated FABP formation which increased in concentration as induced by something in bile that accounts for the improved utilization of unsaturated fatty acids from corn oil as compared to the more saturated types dominating the composition of tallow.…”
Section: Discussionmentioning
confidence: 98%
“…However, when the concentration of the total RNA templates was lowered to 10 ng/25 mL, marked differences occurred in the brightness of bands and the ratio between broiler and layer (Figs. [6][7][8][9].…”
Section: Reprintsmentioning
confidence: 98%
“…L-FABP, I-FABP, A-FABP, muscle (M-) FABP, retinal (R-) FABP have been isolated in the chicken (6)(7)(8)(9)(10), and the chicken liver basic FABP and L-FABP genes have been cloned and sequenced (GenBank accession no. AF380998, AF380999).…”
Section: Introductionmentioning
confidence: 99%